Impact of Concomitant Cardiovascular Medication on Survival of Metastatic Renal Cell Carcinoma Patients Treated with Sunitinib or Pazopanib in the First Line - Fiala, Ondřej; Ostašov, Pavel; Rozsypalová, Aneta; Hora, Milan; Šorejs, Ondřej; Šustr, Jan; Bendová, Barbora; Trávníček, Ivan; Filipovský, Jan; Fínek, Jindřich; Büchler, Tomáš (Targeted oncology, 2021)
BACKGROUND: Patients with metastatic renal cell carcinoma (mRCC) are often elderly and have various comorbidities, including cardiovascular diseases. Although these patients have extensive co-exposure to targeted therapy and cardiovascular drugs, the impact of this co-exposure on outcomes for patients with mRCC remains unclear. OBJECTIVE: Our objective was to evaluate the association between the use of cardiovascular medication and survival of patients with mRCC. METHODS: The study included 343 consecutive patients with mRCC treated with sunitinib or pazopanib in the first line. Clinical data obtained from the Renal Cell Carcinoma Information System (RENIS) clinical registry and hospital information systems were retrospectively analyzed. Progression-free survival (PFS) and overall survival (OS) were compared according to the use of common medications, including antihypertensives (i.e., β-blockers [BBs], angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, calcium channel blockers, and diuretics), acetylsalicylic acid (aspirin), statins, and proton pump inhibitors. RESULTS: The univariate Cox analysis evaluating the impact of the assessed comedications on patient survival revealed that only BBs were significantly associated with PFS (hazard ratio [HR] 0.533, p < 0.001) and OS (HR 0.641, p = 0.006). The median PFS and OS for users of BBs was 18.39 and 37.60 months versus 8.16 and 20.4 months for patients not using BBs (p < 0.001 and p < 0.001, respectively). The Cox multivariate analysis showed that the use of BBs was a significant factor for both PFS (HR 0.428, p = 0.001) and OS (HR 0.518, p = 0.001). CONCLUSIONS: The results of this retrospective study suggest that the use of BBs is associated with favorable outcomes for patients with mRCC treated with sunitinib or pazopanib in the first line.
Keywords: výsledek terapie; Sulfonamides; Sunitinib; nádory ledvin; Disease-Free Survival; Cardiovascular Agents; Indazoles; Pyrroles; retrospektivní studie; karcinom z renálních buněk; indoly; kardiovaskulární látky; indazoly; Kidney Neoplasms; Pyrimidines; Aged; senioři; pyrroly; sunitinib; Treatment Outcome; lidé; Humans; Indoles; pyrimidiny; Carcinoma, Renal Cell; Retrospective Studies; sulfonamidy; přežití bez známek nemoci